Eficiência operacional no âmbito das knowledge-intensive business services: uma análise dos impactos da ação governamental em instituições de ensino técnico profissionalizante - Oliveira, Fabiano Cardoso de (Universidade do Vale do Rio dos Sinos, 2018)
Providing public services with quality and efficient has induced the government to interfere in the private companies’ operations by programs, contracts and partnerships. However, researches about the impacts of these interventions about the efficiency in operations were not found in the literature. This project studies the impact of the PRONATEC program in the efficiency of two knowledge-intensive services companies, one of them is a program participator, and the other it is not a program participator. The impacts were longitudinally analyzed for seven years, using an associated way the Data Envelopment Analysis and the Analysis of Variance in a case study in two companies which are focused in vocational technical education from Rio Grande do Sul, from 2009 to 2015, focused on analyze the production of operational result and training of students. From the results, it is verified the impact of the Government action on the efficiency in the operations of companies that provides knowledge-intensive services.
Keywords: Programas de governo; Eficiência; PRONATEC; Análise envoltória de dados (DEA); Knowledge-intensive Business Services (KIBS); Government programs; Efficiency; PRONATEC; Data Envelopment Analysis (DEA); Knowledge-intensive Business Services (KIBS); ACCNPQ::Ciências Sociais Aplicadas::Administração